Ludwigia humboldtiana (Onagraceae), a narrowly endemic new species from the subtropical Atlantic Forest, southern Brazil - Funez, Luís Adriano; Farias, David Moura; Hassemer, Gustavo; de Gasper, André Luís (Phytotaxa, 2020)
In this work we describe Ludwigia humboldtiana, an extremely narrowly endemic new species from a waterfall system in Corupá municipality, Santa Catarina, southern Brazil. This is already the second plant species endemic to the area. The new species is morphologically most similar to L. caparosa, L. elegans, L. multinervia and L. peruviana but differs from those by a series of taxonomically important characters. We present field photographs, a distribution map and a detailed morphological account of the new species, discuss its morphology and taxonomy in relation to the morphologically most similar other species of Ludwigia, and assess its conservation status according to IUCN criteria.